Analisis Efek Tortuositas pada Heatsink Berpori terhadap Perpindahan Panas Konveksi Alami - Imam Akbar; Ahmad Malik Abdul Aziz; Hariman Al Faritzie; Dewi Rawani (Universitas Sriwijaya, 2023)
This research aims to analyze the effect of tortuosity porous heatsink on natural convection heat transfer. Heatsink plays a crucial role in dissipating heat from electronic components, and optimizing heatsink design is essential for effective and efficient thermal management. In this study, heatsink structures including splitP, diamond, gyroid, and pin were created using generative design methods, and the relationship between tortuosity and heatsinks thermal performance was investigated through Computational Fluid Dynamics (CFD). The results show that an increase in tortuosity leads to a significant increase in surface area and pressure drop, with values ranging from 9298.48-12711.93 mm2 and 0.08701-0.09474 Pa, respectively. Additionally, tortuosity also exhibits a strong linear correlation with the Nusselt number, with value R2=0.88. As tortuosity increases, the Nusselt number decreases significantly from 18.04-9.90. In this research, we conclude that tortuosity is an important parameter that affects heatsink performance, and the TPMS structure we developed is a promising heatsink design candidate for thermal management devices. However, a balance needs to be sought between surface area, pressure drop, overall heat transfer, and other parameters such as pore size and interconnectivity to achieve optimal heatsink performance.